Pengaruh Daya Penyinaran Gelombang Mikro Terhadap Karakteristik Pembakaran Droplet Minyak Jarak Pagar - Dewi, Ray; Wardana, ING; Hamidi, Nurkholis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
The objective this research is to investigate the effect of microwave irradiation power on the combustion characteristics of Jatropha curcas oil. Jatropha Curcas oil is one of alternative fuel. Some advantages of this oil are environmentally friendly, not included in food which can be consumed and renewable. But it can not be use directly because it has a long chemical chain with several double bonds and the viscosity and flash point are very high. One method to improve the combustion characteristics of Jatropha curcas oil, is to irradiate this oil with microwaves. This is due to the energy of microwaves can be absorbed by water, fats and sugars that can affect the Jathropa Curcas oil. The microwave frequency used is 2.45 GHz. Microwave irradiation power is given to the jatropha oil are 119 watt, 252 watt, 385 watt, 539 watt and 700 watt, and the time given 15 minute. And droplet diameter used is 1.5 - 2 mm. From this research was found that microwave can change the viscosity, visualization and dimension of the flame, increase the burning rate, percentage of microexplosion, accelerate the appearance and prolong the duration of microexplosion.Keywords: microwave irradiation, combustion characteristic,droplet